2013
DOI: 10.1111/imm.12128
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II allele polymorphism in an outbreak of chikungunya fever in Middle Andaman, India

Abstract: A sudden upsurge of fever cases with joint pain was observed in the outpatient department, Community Health Centre, Rangat during JulyAugust 2010 in Rangat Middle Andaman, India. The aetiological agent responsible for the outbreak was identified as chikungunya virus (CHIKV), by using RT-PCR and IgM ELISA. The study investigated the association of polymorphisms in the human leucocyte antigen class II genes with susceptibility or protection against CHIKV. One hundred and one patients with clinical features sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Moreover, the amount or type of CHIKV infection present in different individuals could play a role in the emergence of different clinical manifestations. Lastly, host immunogenetics could be another factor influencing the differences observed in CHIKV infection [45,46].…”
Section: Il-17amentioning
confidence: 99%
“…Moreover, the amount or type of CHIKV infection present in different individuals could play a role in the emergence of different clinical manifestations. Lastly, host immunogenetics could be another factor influencing the differences observed in CHIKV infection [45,46].…”
Section: Il-17amentioning
confidence: 99%
“…Many chronic diseases and their host's interaction with the disease have been studied to understand their immunogenetics. HLA-DR3 (HLA- DRB1 * 0301, DQB1 * 0201) and DR4 (HLA-DRB1 * 04, DQB1 * 0302) are markers for type 1 diabetes in Caucasian populations, but not among Japanese patients ( 78 ). The DRB1 * 07 allele is associated with protection against Dengue virus infection in the Cuban population, but not in the Sri Lankan population ( 79 , 80 ).…”
Section: Host Genetics and Chikungunyamentioning
confidence: 99%
“…Human leukocyte antigens (HLA) play a major role in adaptive immune response initiation and have been reported to be associated with disease outcome (reviewed in Dendrou et al 2018). Polymorphisms in genes encoding HLA class II molecules, which present peptides to CD4+ T cells, were examined to determine the effect on susceptibility or protection against CHIKV-induced disease (Chaaithanya et al 2013); HLA-DQ molecules were found to bind more CHIKV peptides than HLA-DRB1 molecules, and HLA-DQB1*03:03 and other HLA-DQB1 genotypes containing glutamic acid at position 86 of peptide-binding pocket 1 were found at a lower frequency in CHIKV patients compared to the control population. Toll-like receptors (TLRs) that recognize viral RNA genomes, including TLR-3, TLR-7, and TLR-8, are key activators of the innate immune response, including pro-inflammatory cytokine induction.…”
Section: Alphavirus Pathogenesis In Humansmentioning
confidence: 99%